2009
DOI: 10.2174/092986709788453078
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronidase Inhibitors: A Biological and Therapeutic Perspective

Abstract: The hyaluronidases (HAases) are a group of less extensively studied glycosidases distributed throughout the animal kingdom and are popularly known as 'spreading factors'. In recent years, HAases received much attention due to their ability to abruptly alter the hyaluronic acid (HA) homeostasis. HAases preferentially degrade HA, which is a megadalton acidic structural polysaccharide found exclusively in the extracellular matrix (ECM) of animals. The HA-HAase system has been suggested to participate in many path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
89
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(103 citation statements)
references
References 190 publications
1
89
0
4
Order By: Relevance
“…Thus, the high activity of F3 could be attributed to its uronic acids content. In addition, the presence of sulfated glycans in this fraction (Table 1) This observation can affirm the hyaluronidase inhibitory effect of F3 fraction, since, as a hyaluronidase inhibitor, it can deter HA fragmentation which can promote inflammation (Girish et al, 2009). In line with this observation, sulfated hyaluronic acid (sHA) (Benitez et al, 2011;Furusawa et al, 2011) was found out to inhibit the activity of hyaluronidases by a mixed inhibition mechanism, where the tumor-derived hyaluronidase was found out to be inhibited by sHA, a nontoxic hyaluronidase inhibitor.…”
Section: Hyaluronidase Inhibitory Effects Of Polysaccharide Fractionsmentioning
confidence: 55%
See 2 more Smart Citations
“…Thus, the high activity of F3 could be attributed to its uronic acids content. In addition, the presence of sulfated glycans in this fraction (Table 1) This observation can affirm the hyaluronidase inhibitory effect of F3 fraction, since, as a hyaluronidase inhibitor, it can deter HA fragmentation which can promote inflammation (Girish et al, 2009). In line with this observation, sulfated hyaluronic acid (sHA) (Benitez et al, 2011;Furusawa et al, 2011) was found out to inhibit the activity of hyaluronidases by a mixed inhibition mechanism, where the tumor-derived hyaluronidase was found out to be inhibited by sHA, a nontoxic hyaluronidase inhibitor.…”
Section: Hyaluronidase Inhibitory Effects Of Polysaccharide Fractionsmentioning
confidence: 55%
“…At the same time, sHA also delineated the molecular mechanism through which hyaluronic acid-hyaluronidase (HA-HAase) system might mediate tumor growth and progression, since HA-HAase is known to promote tumor growth and metastasis (Simpson & Lokeshwar, 2008). Hence, inhibition of HA degradation appears critical and imperative in HAase mediated pathological conditions (Girish et al, 2009). …”
Section: Hyaluronidase Inhibitory Effects Of Polysaccharide Fractionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosmarinic acid, lithospermic acid B, diosmetin-7-O-b-D-glucuronide, and apigenin-7-O-b-D-glucuronide were identified as hyaluronidase inhibitors. Two new cyclic spermidine alkaloids, meefarnines A and B (1, 2), four new flavone glycosides, fargenins A-D (3)(4)(5)(6), and the methyl ester (4a) of 4 have also been isolated together with 10 known compounds and we describe the elucidation of their structure.…”
mentioning
confidence: 99%
“…3,4) Moreover, they are potent anti-inflammatory, anti-aging, and anti-cancer agents. 5) In the present study, we investigated constituents of fractions which showed strong hyaluronidase inhibitory activity from whole plants of M. fargesi. Rosmarinic acid, lithospermic acid B, diosmetin-7-O-b-D-glucuronide, and apigenin-7-O-b-D-glucuronide were identified as hyaluronidase inhibitors.…”
mentioning
confidence: 99%